MEASURING EMPLOYEE PERFORMANCE WITH THE HUMAN RESOURCE SCORECARD APPROACH PT MATAHARI DEPARTMENT STORE CIPUTRA CIBUBUR - Nuraeni Nuraeni; Muhammad Sidik; Rifzaldi Nasri; M. Yusuf (ABNUS Publisher, 2021)
This study aims to identify and develop employee performance measurement using the Human Resources Scorecard approach. This performance measurement is to determine the level of success of the Human Resources Division's strategy which has been measured using the Key Performance Indicator / Performance Appraisal by PT Matahari Department Store Ciputra Cibubur. The research method used is qualitative and quantitative analysis. In this study, a strategic map for the Human Resources division was designed and the success indicators of each strategic objective and performance measurement of human resources were identified using the